Peran Guru dan Standar Proses Pembelajaran atas Keberhasilan Prestasi Belajar Siswa - Faridah, Zeni (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2023)
Education is a very important element and cannot be ignored in the world of education which currently acts as a facilitator for students because the role of the teacher is one of the things that determines the success or failure of a teaching and learning process. Therefore, in the education and learning process it is necessary to provide qualified teachers, meaning that apart from mastering the subject matter, and teaching methods, they also understand the Learning Process Standards. (SPP). The purpose of this research is to use a literature study with a descriptive qualitative approach, data was collected through text study and results from relevant research. By using extracts from several sources from several journals, books, and others. The research results show that good learning and meeting standards will produce high-achieving students. Achievement is a skill or concrete result that can be achieved at a certain time or period. Based on this opinion, achievement in this research is the result that students have achieved in the learning process.